The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/153303461000900202
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs: Identification of Cancer-Associated microRNAs by Gene Profiling

Abstract: MicroRNAs (miRNAs) belong to the heterogeneous class of non-coding RNAs (ncRNAs), which are by definition RNA molecules that do not encode for proteins, but have instead important structural, catalytic or regulatory functions. In this review we first provide an overview of the different ncRNA families, focusing in particular on miRNAs and their relevance in tumour development and progression. Second we shortly describe the available ncRNA expression profiling methods, which comprise microarray, bead-based hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 123 publications
0
41
0
Order By: Relevance
“…Unique miRNA sequences are detected in corresponding healthy and malignant tissues [77]. More than 50% of all miRNAs in humans are located in sensitive regions of chromosomes that undergo amplification, deletion and translocation during carcinogenesis [78,79].…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…Unique miRNA sequences are detected in corresponding healthy and malignant tissues [77]. More than 50% of all miRNAs in humans are located in sensitive regions of chromosomes that undergo amplification, deletion and translocation during carcinogenesis [78,79].…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…[6][7][8] In addition, alterations in miRNA expression have been described in many different human tumors, and numerous studies have demonstrated that miRNAs function as key pathogenic components impacting cancer cell growth, survival and the capacity to metastasize. 7,[9][10][11][12][13] Furthermore, miRNAs serve as instructive molecular surrogates in the distinction of benign from malignant as well as in prognostic algorithms of outcome in various tumor types. [14][15][16] Finally, it is feasible to obtain high-quality miRNA expression data from formalin-fixed paraffin-embedded (FFPE) melanomas-often the only tissue available for retrospective analyses.…”
mentioning
confidence: 99%
“…The biogenesis of miRNAs is well documented (Figure 1) and the involvement of miRNAs in regulation of cancer-related events is well established [28] . These small non-coding RNAs are believed to be involved in every single aspect of the development and progression of human cancers.…”
Section: Brief Overview Of Micrornas (Mirnas)mentioning
confidence: 99%